2022
DOI: 10.5194/acp-22-2237-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Long-term measurements of aerosol precursor concentrations in the Finnish subarctic boreal forest

Abstract: Abstract. Aerosol particles form in the atmosphere via the clustering of certain atmospheric vapors. After growing into larger particles by the condensation of low-volatility gases, they can affect the Earth's climate by scattering light and acting as cloud condensation nuclei (CCN). Observations of low-volatility aerosol precursor gases have been reported around the world, but longer-term measurement series and any Arctic data sets showing seasonal variation are close to nonexistent. Here, we present ∼7 month… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
3
8
0
Order By: Relevance
“…The daytime increase can be explained by sunny conditions warming the air during the day. This trend is similar to what Jokinen et al (2022) observed in northern Finland.…”
Section: Factors Favouring Npf Event Occurrencesupporting
confidence: 91%
“…The daytime increase can be explained by sunny conditions warming the air during the day. This trend is similar to what Jokinen et al (2022) observed in northern Finland.…”
Section: Factors Favouring Npf Event Occurrencesupporting
confidence: 91%
“…As for the two iodine oxoacids (HIO3 and HIO2), daytime mean concentration of HIO3 is more than one order of magnitude higher than HIO2. The one order of magnitude lower HIO3 concentration compared with H2SO4 in summer at both sites is consistent with that in the Finnish subarctic boreal forest (Jokinen et al, 2022).…”
Section: Overview Of the Measurementsupporting
confidence: 85%
“…On the other hand, HIO3 concentrations in Beijing and Nanjing are comparable to that in Helsinki, Finland. Measurements at SMEAR III station, an urban site located in University of Helsinki show HIO3 concentrations at around 10 6 cm -3 when the wind is coming from land for most times in August and HIO3 concentrations exceed 365 10 7 cm -3 when air masses have marine origin (Thakur et al, 2022;He et al, 2021b). Another long-term observation conducted at SMEAR I station (Jokinen et al, 2022), a subarctic boreal forest site, shows HIO3 concentrations often at around 10 5 cm -3 from April to November 2019 (summer and autumn) with occasional peaks exceeding 10 6 cm -3 in late August.…”
Section: Seasonal Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of new particles was observed and investigated in various geographic locations under different atmospheric and environmental conditions, from which common characteristics and different peculiarities emerged (Baalbaki et al, 2021;Jokinen et al, 2022;Yadav et al, 2021;Franco et al, 2022).…”
Section: Introductionmentioning
confidence: 99%